Development of Thermophilic Tailor-Made Enzyme Mixtures for the Bioconversion of Agricultural and Forest Residues - Karnaouri, Anthi; Matsakas, Leonidas; Topakas, Evangelos; Rova, Ulrika; Christakopoulos, Paul (Frontiers in Microbiology, 2016)
Even though the main components of all lignocellulosic feedstocks include cellulose, hemicellulose, as well as the protective lignin matrix, there are some differences in structure, such as in hardwoods and softwoods, which may influence the degradability of the materials. Under this view, various types of biomass might require a minimal set of enzymes that has to be tailor-made. Partially defined complex mixtures that are currently commercially used are not adapted to efficiently degrade different materials, so novel enzyme mixtures have to be customized. Development of these cocktails requires better knowledge about the specific activities involved, in order to optimize hydrolysis. The role of filamentous fungus Myceliophthora thermophila and its complete enzymatic repertoire for the bioconversion of complex carbohydrates has been widely proven. In this study, four core cellulases (MtCBH7, MtCBH6, MtEG5 and MtEG7), in the presence of other four “accessory” enzymes (mannanase, lytic polyssacharide monooxygenase MtGH61, xylanase, MtFae1a) and β-glucosidase MtBGL3, were tested as a 9-component cocktail against one model substrate (phosphoric acid swollen cellulose) and four hydrothermally pretreated natural substrates (wheat straw as an agricultural waste, birch and spruce biomass, as forest residues). Synergistic interactions among different enzymes were determined using a suitable design of experiments methodology. The results suggest that for the hydrolysis of the pure substrate (PASC), high proportions of MtEG7 are needed for efficient yields. MtCBH7 and MtEG7 are enzymes of major importance during the hydrolysis of pretreated wheat straw, while MtCBH7 plays a crucial role in case of spruce. Cellobiohydrolases MtCBH6 and MtCBH7 act in combination and are key enzymes for the hydrolysis of the hardwood (birch). Optimum combinations were predicted from suitable statistical models which were able to further increase hydrolysis yields, suggesting that tailor-made enzyme mixtures targeted towards a particular residual biomass can help maximize hydrolysis yields. The present work demonstrates the change from ‘one cocktail for all’ to ‘tailor-made cocktails’ that are needed for the efficient saccharification of targeted feed stocks prior to the production of biobased products through the biorefinery concept.